2023
DOI: 10.1051/0004-6361/202347348
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of H2S with H atoms on grain surfaces under molecular cloud conditions

J. C. Santos,
H. Linnartz,
K.-J. Chuang

Abstract: Context. Hydrogen sulfide (H2S) is thought to be efficiently formed on grain surfaces through the successive hydrogenation of sulfur atoms. Its non-detection so far in astronomical observations of icy dust mantles thus indicates that effective destruction pathways must play a significant role in its interstellar abundance. While chemical desorption has been shown to remove H2S very efficiently from the solid phase, in line with H2S gas-phase detections, possible ice chemistry triggered by the related HS radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 77 publications
(97 reference statements)
3
8
0
Order By: Relevance
“…The second strongest desorption feature in Figure 1 peaks at 131 K and contains the mass signals m/z = 32 and 66 (see Figure 5a). Both the peak desorption temperature and the relative intensities of the fragments are in full agreement with the reference values for disulfane (H 2 S 2 ) 50 (Figure 5b). Moreover, its characteristic SH stretching band is observed on the red wing of the H 2 S feature peaking at ∼2491 cm −1 , as shown in Figure 5c.…”
Section: ■ Results and Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The second strongest desorption feature in Figure 1 peaks at 131 K and contains the mass signals m/z = 32 and 66 (see Figure 5a). Both the peak desorption temperature and the relative intensities of the fragments are in full agreement with the reference values for disulfane (H 2 S 2 ) 50 (Figure 5b). Moreover, its characteristic SH stretching band is observed on the red wing of the H 2 S feature peaking at ∼2491 cm −1 , as shown in Figure 5c.…”
Section: ■ Results and Discussionsupporting
confidence: 84%
“…Indeed, the formation of this species is unsurprising, as it has been previously shown to form at 10 K in an H 2 S ice exposed to H atoms likely as a result of SH radical recombination. 50 Subsequently to H 2 S 2 , a desorption feature appears at 158 K with contributions from m/z = 46, 47, 58, 59, 60, 61, and 94 (Figure 6, left panels). The mass-to-charge ratios of 92, 118, 120, and 122 were also recorded during the TPD experiment, but no increase in their signal was observed above the instrumental detection limit.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, they can take part in efficient hydrogenation reactions in an H-rich environment eventually yielding ˙SH and H 2 S (reactions (R13) and (R10)). 50 It is important to note that Krupa et al showed the exclusive presence of the HCN⋯S complex in the Ar matrix after photolyzing HNCS, 51 which is absent in the para -H 2 matrix (possibly due to the diminished cage effect) but likely exist in the Ar matrix as there is a very weak signal at 3217.8 cm −1 , close to the literature value. Another possibility, which cannot be excluded, is the photodecomposition of H 2 N–CN resulting in the formation of isocyano/cyano resonance structures (˙NC ↔ ˙CN, reaction (R14)).…”
Section: Resultssupporting
confidence: 81%